Correlations between Some Yield and Yield Components in Sunflower Helianthus annuus L. Hybrid, Line and Varieties - Belgin Coşge; Nilgün Bayraktar (Journal of Agricultural Sciences)
This study was conducted on experimental field of Field Crops Department at Agricultural Faculty of Ankara University in 1995, 1997 and 1998. The trials were designed in randomized block design with three replications. Genetic male sterile lines, hybrids and Ekiz-1, Vn ıı mk-8931 and Super-25 varieties were used as a material. According to the results of correlation analysis; positive correlations between SeY, SY, HD and PH; between OR, TSW, SeY and HD; between SeY, TSW and SY were recorded.